Precocious puberty under stressful conditions: new understanding and insights from the lessons learnt from international adoptions and the COVID-19 pandemic - Street, Maria Elisabeth; Ponzi, Davide; Renati, Roberta; Petraroli, Maddalena; D’Alvano, Tiziana; Lattanzi, Claudia; Ferrari, Vittorio; Rollo, Dolores; Stagi, Stefano (Frontiers in Endocrinology, 2023)
From a neuro-biological point of view, variations in the timing of sexual maturation within a species are part of an evolved strategy that depends on internal and external environmental conditions. An increased occurrence of central precocious puberty (CPP) has been clearly described in both adopted and “covid-19 pandemic” children. Whereas the causes of CPP in internationally adopted children advocated until now encounter improved nutritional and environmental conditions, as well as supposedly improved psychological conditions, during and after the coronavirus disease 2019 (COVID-19) global pandemic other possibilities must be considered. In a society where there are good living conditions, a threat for life as that presented initially by the pandemic or other stressful conditions related to it, could easily trigger from an evolutionary point of view, a condition of early pubertal maturation to favour early reproduction. The main driver for precocious and rapidly progressive puberty could well stand in a condition of “fear and stress” that must have been present in schools during the pandemic (i.e. no social contact, use of DPI, fear of getting ill), families (small houses, smart-working, loosing jobs, etc) or both. The features of puberty and time of progression are similar to those observed in adopted children. In this review we analyse precocious puberty both during the pandemic and in internationally adopted children, and try to retrace the physiological and evolutionary factors underlying puberty by focusing on the stress factor and its correlation with an early activation of the hypothalamic-pituitary-gonadal axis besides with a rapid process of maturation.